2005
DOI: 10.1074/jbc.m407384200
|View full text |Cite
|
Sign up to set email alerts
|

TRPC1-mediated Inhibition of 1-Methyl-4-phenylpyridinium Ion Neurotoxicity in Human SH-SY5Y Neuroblastoma Cells

Abstract: Mammalian homologues of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
84
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(94 citation statements)
references
References 53 publications
9
84
1
Order By: Relevance
“…Vybrant Staining Assay-Vybrant staining assay was used to evaluate apoptosis, using the method described previously (24).…”
Section: Methodsmentioning
confidence: 99%
“…Vybrant Staining Assay-Vybrant staining assay was used to evaluate apoptosis, using the method described previously (24).…”
Section: Methodsmentioning
confidence: 99%
“…However, although it is apparent that ER stress plays a major role in neurodegeneration, the mechanism by which these neurotoxins induce ER stress is not known. Previously we reported that transient receptor potential channel 1 (TRPC1) is critical for neuronal survival and that MPP + treatment decreases TRPC1 expression in SH-SY5Y and PC12 cells (18,19); however, the mechanism is not known.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies showed that activation of TRPC1 by thapsigargin or carbachol decreased MPP1 neurotoxicity Thus TRPC1 may execute a neuroprotective role in dopaminergic neurons. Furthermore, TRPC1 may inhibit degenerative apoptotic signaling to provide neuroprotection against Parkinson's disease-inducing agents [334,335]. …”
Section: Parkinson's Diseasementioning
confidence: 99%